Compound Molecules of Network Pharmacology-Based of Tamarillo (Cyphomandra betacea Cav.) and the Potential as Noodle for Type 2 Diabetes Mellitus Treatment - Fitriyani, Fitriyani; Ningrum, Salsabila E.S.; Mutiah, Rohiatul; Kinasih, Larasati Sekar (Majalah Obat Tradisional, 2023)
Consuming noodles excessively is not good for health because it contains high trans fat, which can cause diabetes mellitus (DM) as a disease with a high prevalence, especially type 2 DM, as much as 95% in Indonesia. Tamarillo (Chypomandra betacea Cav.) can potentially reduce blood glucose levels and restore adipokine regulation to prevent insulin resistance in type 2 DM. This study aims to determine the formulation and potential of tamarillo compounds into noodle products named "Chypotes (Chypomandra Antidiabetes) Noodle" as an alternative food for type 2 DM patients.  The methods used are noodle formulation, organoleptic test, hedonic test, and network pharmacology.  Based on the results of an organoleptic test, Chypotes Noodle has a chewy texture, a distinctive smell, yellow colour, and a slightly sour tasteless taste typical of Tamarillo. Based on the results of the hedonic test, 30 respondents chose the like and very like options in filling out the questionnaire with a percentage of 80-90%. Based on the Network Pharmacology of Tamarillo shows that 150 of the 365 target proteins of Tamarillo are involved in the biological processes and signaling pathways of type 2 diabetes mellitus, with 75 target proteins locking and interacting. Compound Molecules of Tamarillo, such as six bioactive components of the hydroxycinnamic acids group, have activity in type 2 DM and affect the biological processes and signaling pathways of type 2 DM against ADIPOQ, TNF, and INS. Therefore, Tamarillo can potentially be used as an alternative food product in the form of noodles for type 2 DM treatment.